Decision-Making in Sport During a Pandemic. Issue 6 (November 2021) - Hamilton, Bruce; Burt, Peter; Anderson, Lynley
Abstract : Objective: The COVID-19 pandemic has affected all elements of global society, and sport is not exempt. Many sporting events have been either postponed or canceled, and national sporting organizations have had to make highly complex decisions in the face of scientific uncertainty and risk. This article applies these lessons to the world of sport with the goal of assisting sporting organizations to make sound and reasoned decisions during a pandemic. Data Sources: A narrative approach using both academic literature sources and live examples from the authors' experience. We use Daniels and Sabin's accountability for reasonableness framework to facilitate decision-making in the face of such uncertainty. Main Results: Decision-making in the context of uncertainty has the potential to create conflict and disengagement from key stakeholders. Evidence from recent pandemics has illustrated that an ethical approach to decision-making results in reasoned decision-making and confers a legitimacy to decisions that ultimately supports engagement and satisfaction from stakeholders. Conclusions: The incorporation of ethical considerations into risk assessment and management when making complex decisions, which incorporate high levels of uncertainty, will assist sporting organizations have positive outcomes.